2021
DOI: 10.1038/s41467-021-27445-8
|View full text |Cite
|
Sign up to set email alerts
|

Changing impacts of Alaska-Aleutian subduction zone tsunamis in California under future sea-level rise

Abstract: The amplification of coastal hazards such as distant-source tsunamis under future relative sea-level rise (RSLR) is poorly constrained. In southern California, the Alaska-Aleutian subduction zone has been identified as an earthquake source region of particular concern for a worst-case scenario distant-source tsunami. Here, we explore how RSLR over the next century will influence future maximum nearshore tsunami heights (MNTH) at the Ports of Los Angeles and Long Beach. Earthquake and tsunami modeling combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…3). It appears that for the Semidi section, a sizeable (M8.2) earthquake temporarily perturbed the state of slip and stress on the megathrust, but it probably did not leave the shallower portion of the megathrust in any more of a primed state to slip in a major trench-rupturing Pacific basin-wide tsunamigenic earthquake than before (80,81). Although some of the long-term slipdeficit in the Semidi section (39) was recovered by the Chignik event, it is clear that the potential for a much larger, 1788-type earthquake still dominates the hazard for the Semidi section (39,43,46,47).…”
Section: Discussionmentioning
confidence: 98%
“…3). It appears that for the Semidi section, a sizeable (M8.2) earthquake temporarily perturbed the state of slip and stress on the megathrust, but it probably did not leave the shallower portion of the megathrust in any more of a primed state to slip in a major trench-rupturing Pacific basin-wide tsunamigenic earthquake than before (80,81). Although some of the long-term slipdeficit in the Semidi section (39) was recovered by the Chignik event, it is clear that the potential for a much larger, 1788-type earthquake still dominates the hazard for the Semidi section (39,43,46,47).…”
Section: Discussionmentioning
confidence: 98%
“…This extreme risk and recent experience, including rebuilding and adapting to tsunami risk, may overpower concerns about smaller SLR projections of between 1 and 2 meters. However, tsunami risk greatly increases with SLR and therefor SLR ought not to be ignored 44 . Other places, such as Western Africa, where none of our respondents said that SLR is part of planning, could be stymied by a lack of capacity for long-term planning (e.g., 2100 and beyond) and rather Title: A Global Survey of the Application of Sea-Level Projections Primary Manuscript 6 focus on the near term (i.e., next 10 -20 years).…”
Section: Regionally (Fig 1b and Supplementary Tablementioning
confidence: 99%
“…More recently, Dura et al (2021) [14] conducted an earthquake and tsunami modelling analysis that combined local probabilistic RSLR projections to show the increased potential for more frequent, relatively low magnitude earthquakes (Mw 8.0) originating at the Alaska-Aleutian subduction zone, to produce distant-source tsunamis that exceed historically observed maximum nearshore tsunami heights at Los Angeles and Long Beach Ports in California. These observations are consistent with nearshore tsunami height changes due to SLR presented by Koyano et al (2022) [15] for the east coast of Japan, who also suggested that the effects of SLR on expected tsunami heights at coast are non-linear and vary according to location.…”
Section: Introductionmentioning
confidence: 99%